The Political Economy of Punishment Today: Visions, Debates and Challenges - Brandariz-García, José A.; Melossi, Dario; Sozzo, Máximo (Taylor and Francis, 2018)
"Cover" -- "Half Title" -- "Title Page" -- "Copyright Page" -- "Table of Contents" -- "List of Figures" -- "List of Tables" -- "Contributors" -- "Series editor foreword" -- "Acknowledgements" -- "The political economy of punishment today: An introduction" -- "Chapter 1 Between struggles and discipline: Marx and Foucault on penality and the critique of political economy" -- "Chapter 2: The renaissance of the political economy of punishment from a comparative perspective" -- "Chapter 3 For and against the political economy of punishment: Thoughts on Bourdieu and punishment" -- "Chapter 4 Do economic depressions reduce the use of fines?: Revisiting Rusche and Kirchheimerâ#x80;#x99;s Punishment and Social Structure" -- "Chapter 5 From one recession to another: The lessons of a long-term political economy of punishment. The example of Belgium (1830â#x80;#x93;2014)" -- "Chapter 6 Political economy of punishment in Australia" -- "Chapter 7 Punishment in a hybrid political economy: The Italian case (1970â#x80;#x93;2010)" -- "Chapter 8 â#x80;#x98;A return to Gulagsâ#x80;#x99;?: Explaining trends in post-Soviet prison rates" -- "Chapter 9 Inclusionâ#x80;#x99;s dark side: The political economy of irregular migration in Greece" -- "Chapter 10 Reflections on Spanish policies of migration control: A political economic reading on the punishment of migrants".